Iodine-131 Combined With Plasma Exchange Treatment in Graves’ Hyperthyroidism Patients With Severe Liver Injury Whose Average Model for End-Stage Liver Disease Scores >20 - Xin-Fang Zhu; Rong-Rong Ding; Bing-Yao Wang; Yun-hui Yang; Fu-Xia Ta; Yuan Wang; Qing-Mei Gao; Qi Zhang; Rong Xia; Xing-Guang Luo; Xuan Wang; Jian-Ming Zheng; et al. (Gastro Hep Advances)
Background and Aims: The purpose of this retrospective study is to describe the Graves’ hyperthyroidism patients with severe liver injury treated by iodine-131 combined with plasma exchange (PE). Methods: The patients who had hyperthyroidism caused by Graves’ disease, with severe liver injury (The level of total bilirubin ≥12 mg/dL), and after 1 week of liver protective medication treatment, the patient’s liver function did not improve, were enrolled in this study. All patients were treated with iodine-131 and PE. The patients’ laboratory data after 3 months of isotope therapy were collected. Results: In this study, there were 8 patients included, the average model for end-stage liver disease (MELD) scores were greater than 20 (ranges from 19 to 30) at baseline. The levels of hemoglobin, platelet count, alanine aminotransferase, aspartate aminotransferase, total bilirubin, direct bilirubin, alkaline phosphatase, glutamyl transpeptidase, MELD scores, free triiodothyronine, free thyroxine, antithyroid peroxidase autoantibody and serum thyrotropin receptor antibodies after PE treatment were significantly lower than before PE treatment (P < .05). The level of total bilirubin at 3 months post-131I treatment was significantly lower than pre-131I treatment (P = .0200), the same was the level of direct bilirubin (P = .0200). Conclusion: Our study enrolled Graves’ hyperthyroidism patients with severe liver injury whose average MELD scores were greater than 20, and shows that liver function test can recover on about 3 months treated iodine-131 combined with PE therapy.